Coping with work stress : a review and critique - Dewe, Philip J.; O'Driscoll, Michael P.; Cooper, Cary L. (Wiley, 2010)
Coping With Work Stress: A Review and Critique highlights the most up-to-date research relating to effective coping strategies of individuals and organizations and provides a series of invaluable best practice techniques for dealing with the growing epidemic of stress and lack of overall well-being at work. The authors -- renowned experts in the field -- offer their carefully considered critical reviews of issues surrounding the latest work stress and coping studies and identify several new strategic pathways to stimulate future research.
Keywords: Job stress; Stress management; työ; stressi; stressinhallinta; jaksaminen